ACADEMIC ADAPTATION OF DISPLACED CHILDREN: A CASE STUDY OF A MIXED-AGED CLASS IN GERMANY - Olena Moskalets; Olena Gryshchenko; Galyna Tsapro; Olga Tsapro (Borys Grinchenko Kyiv Metropolitan University, 2024)
The paper focuses on the initial experience of a mixed-aged group of newly arrived Ukrainian children and their new Ukrainian teacher at a school in Germany. To assess the efficiency of the first four months of the transition period and to outline the recommendations for the further steps in teaching the Ukrainian asylum seekers a mixed method study including qualitative and quantitative analysis was applied. Interviews with the acting Ukrainian teacher, her reflective analysis of the observations of her group of 26 Ukrainian children aged 11-16, indirect feedback collected from the local teachers involved in working with the learners, as well as the answers to two mixed anonymous questionnaires conducted on the twenty learners who consented to participate were used to collect data on the interim outcomes of the transition period. In-class interaction and communication with the teacher, along with the desire to socialize and make new interpersonal connections, were among the most significant factors in fostering positive experiences and engagement for children in school. Learners mentioned up to six subjects lacking in their German schools, with mathematics being the most frequently cited, some students desired additional language classes, including Ukrainian, English, and German. The organization of the initial four-month-long stage of the transition period has served the purpose of providing young asylum seekers with sufficient psychological support and an opportunity to get back to normal life. In the upcoming academic year, it is urgent to establish clear academic expectations, avoid treating children as overly special, and prioritize their integration into society.